Does GPA matter for university graduates' wages? New evidence revisited. - Tao Zou; Yue Zhang; Bo Zhou (PLoS ONE)
This paper examines the effect of GPA on graduating students' wages using a data set from an elite university in China. Students are homogenous since their majors are closely related to economics and business The OLS regression results indicate that GPA has positive and significant impacts on wages on average. As GPA increases by 1 unit, the starting monthly wage increases by 29.6 percent on average, and the wage in the survey year that is 3-5 years after graduation (current wage) soars by 25 percent. Theoretically, the GPA matters for the wages due to both the human capital or signaling effect. Given that the signaling effect should diminish over time, and the effect on starting wage is a little larger than that on current wage, it is suggested that signaling effect of GPA should be trivial, and high GPA is associated with high wage should be mainly due to the human capital effect. These results are robust to different model specifications. The distributional analysis suggest that the effects are positive for both wages and significant for almost all quantiles. In addition, the effect is basically the same from the 0.05th to 0.80th quantiles, and then rises as the starting wage increases. The effect on current wage is a U shape from the 0.05th to 0.60th quantile, and then becomes an inverse-U shape with peaks at the 0.75th and 0.80th quantiles where the effect is 82.2 percent when GPA increases by one unit.